PENERAPAN TEKNOLOGI SMART BUILDING PADA PERANCANGAN SMART MASJID - Mannan, Khalid Abdul; Muchlis, Aulia Fikriarini (Journal of Islamic Architecture, 2012)
Indonesia has the largest Muslim population in the world, followed by a large number of mosques scattered invarious places and these mosques sometimes have a problem regarding the efficiency in managing theresources of a mosque. This paper is designed to introduce the concept of mosque design based on theprinciples of smart building with the literature study methods and analysis, and comparison to the values in thephilosophy of the Qur'an to determine the suitability of the application of smart building technology in thedesign of a mosque. With the support of some religious activities program, the expected result is "smartmosque", that would also suit withÂ  the site and user.